Generalization of Titchmarsh's theorems for the Minkowski algebra. Issue 1 (2nd January 2023) - El Haoui, Youssef; Zayed, Mohra
Abstract : The Minkowski space–time algebra C ℓ 3, 1 is a powerful tool for studying the theory of electromagnetism and special relativity. In this paper, we intend to establish generalizations of Titchmarsh theorems for certain classes of functions, namely Lipschitz functions in the space L p ( R 3, 1, C ℓ 3, 1 ) for 1 < p ≤ 2 .